Une mobilité transfrontalière sous contrôle ? Le cas turco-syrien en temps de guerre (2011-2015) - Matthieu Cimino (L'Espace Politique)
Since the beginning of the Syrian revolution (2011), the Turkish-Syrian border is undergoing profound changes. Although this borderland is essentially studied through a military perspective due to Daesh threat in the region, it is still deeply reconfigured by new circulatory dynamics, and by the State reaction and procedures that accompany them. Using three analytical levels, this article aims to question border management practices implemented by the Turkish government since the beginning of the crisis, and to extract the empirical and symbolic consequences on Turkish-Syrian cross-border space. For this, we will first study the opening and closing phases of the border (1), the illegal trade management dynamics (2) and, finally, a case study of a cross-border mobilization at Suruç-Kobani (3).